Needs for Changes of teaching and learning English - Yoon, Tecnam (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The purpose of this editorial article is intended to provide pre- and in-service teachers with useful suggestions in terms of teaching English in an EFL setting. Because learners of today take in and process information in very different ways, ways of teaching or instructing needs to be deifferntiated accordingly. In fact, there is no doubt that learners academic performance and efficacy towards learning is mostly determined by teaching styles of a teacher. In other words, effets or results of learning may be varied based on teaching method. In terms of English education, both pre- and in-service English teachers, therefore, should consider which methods may fit well into the class in order for learners to fulfill the ultimate goals of learning English. This paper proposes how and why to adapt computer assisted learning.